2004
DOI: 10.1590/s0100-40422004000600004
|View full text |Cite
|
Sign up to set email alerts
|

Fotoluminescência e adsorção de CO2 em nanopartículas de CaTiO3 dopadas com lantânio

Abstract: Recebido em 12/6/03; aceito em 27/5/04; publicado na web em 27/8/04 PHOTOLUMINESCENCE AND CO 2 ABSORPTION ON LANTHANUM DOPED CaTiO 3 NANOPARTICLES. Ca 1-x La x TiO 3 powders were prepared by the polymeric precursor method. X-ray diffraction (XRD), FT-Raman spectroscopy, transmission electron microscopy (TEM), and N 2 and CO 2 adsorption were used for the microstructural and surface characterization of the powders. Room temperature photoluminescence (PL) was observed in Ca 1-x La x TiO 3 amorphous particles. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 12 publications
0
3
0
6
Order By: Relevance
“…Defects in the crystal lattice play an important role in the determination of the luminescent properties of the oxides [26,27]. Therefore, direct changing of the contents of some types of defects may cause variations of concentrations of the corresponding luminescence centers [28,29]. In particular, vacancies are very important in the formation of the luminescence-center structure for such crystals [30,31].…”
Section: Pl Emission Analysismentioning
confidence: 99%
“…Defects in the crystal lattice play an important role in the determination of the luminescent properties of the oxides [26,27]. Therefore, direct changing of the contents of some types of defects may cause variations of concentrations of the corresponding luminescence centers [28,29]. In particular, vacancies are very important in the formation of the luminescence-center structure for such crystals [30,31].…”
Section: Pl Emission Analysismentioning
confidence: 99%
“…Investigations into doping using lanthanum [6], samarium [7], and neodymium [8] in calcium titanates (CT) have been published, but little attention has been paid to praseodymium. Inaguma and co-authors [9] recently reported on structural anomalies that occurred when praseodymium ions with different oxidation states were incorporated into ferroelectric CT materials using the traditional solid-state reaction.…”
Section: Introductionmentioning
confidence: 99%
“…20,25 A partir dos resultados obtidos, fica evidente que a capacidade de adsorção de CO 2 pode ser significativamente afetada pelo processo (tempo) de moagem. A quantidade total e irreversível de CO 2 , determinada para o MgO de partida foi de 3,0 e 2,15 μmol/m 2 , respectivamente.…”
Section: Análise Por Adsorção Química De Co 2 Do Caráter Básico Das Aunclassified
“…13,18 No processo de moagem mecânica de alta energia, apesar da importância do atrito mecânico, o principal mecanismo está muito relacionado com a colisão das esferas com o pó processado. 19,20 Atualmente, estes materiais não-cristalinos podem ser uma alternativa economicamente viável para substituir uma variedade de 3 (titanato de chumbo), um tipo de peroviskita simples, possuem aplicações ópticas que são alvo de estudo neste trabalho. Adicionalmente são apresentadas as mudanças nas propriedades físico-químicas dos óxidos de magnésio e de estanho, respectivamente, dopados com terras raras em função dos processados com moagem mecânica de alta energia.…”
Section: Introductionunclassified
See 1 more Smart Citation